Foucault and Latin America : appropriations and deployments of discursive analysis - Trigo, Benigno (Routledge, 2012)
Foucault and Latin America is the first volume to trace the influence of Foucault's theories on power, discourse, government, subjectivity and sexuality in Latin American thought.